Calves born under tropical conditions after direct transfer of cryopreserved in vitro produced embryos - Nava Trujillo, Héctor; De Ondiz, Aitor; Soto Belloso, Eleazar; Velarde, Juan Carlos; Hernández Fonseca, Hugo; Brackett, Benjamin (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
In the present study, performance of 56 crossbred dual purpose heifers diagnosed as pregnant after direct transfer of in vitro produced embryos cultured in either media supplemented with serum (n = 23) or in a chemically defined media (n = 33) were compared. No differences were observed in the incidence of abortion (30.34% vs. 24.24%), dystocia (52.17% vs. 51.52%) and normal calving (17.39% vs. 24.24%) in pregnant heifers with embryos produced in either serum supplemented or chemically defined media respectively (P > 0.05). Sex of calves affected significantly the rate of dystocia (males, 83.33% and females, 50%; P < 0.05). The birthweight of calves was not affected (P > 0.05) neither by serum supplementation during in vitro culture (46.86 Ó 2.04 kg for calves derived from embryos cultured in the serum supplemented media and 46.28 Ó 1.42 kg, for calves derived from embryos cultured in the chemically defined media) nor by sex of calves (males, 47.20 Ó 1.50 kg and females, 45.45 Ó 1.84 kg). The birthweigh of calves born dead or dying soon after birth was significantly (PÂ < 0.05) higher (51.92Â Ó 1.76 kg) than that of survivors calves (43.88 Ó 1.22 kg). Neither serum supplementation during in vitro culture, sex of calves nor dystocia affected the perinatal survival of calves. In conclusion, the presence of serum during in vitro culture did not affect the reproductive performance of dual purpose pregnant heifers after direct transfer of in vitro produced embryos. Large offspring syndrome (LOS) as observed in this study was evidenced by high birthweigh of calves, high rate of abortions and dystocia.